TANDA DAN GEJALA GASTROPATI NSAID - Vaanipriya Gajapathi Rao (Intisari Sains Medis, 2016)
Introduction: gastritis is the process of inflammatory in the stomach mucous lining and submucous and in histopathology can be evidenced by the infiltration cells of the area. NSAID used to treat rheumatoid arthritis, osteoartritis or pain. NSAID damage gastric mucous through two mechanism that is topical and systemic. Mucous damage in topikal occurred because NSAID are acidic and lipophilic, making it easier trapping hydrogen ions enter the mucosa and cause damage. Systemic effects of NSAIDs are more important that mucosal damage caused by prostaglandin production decreases significantly.Case: The patient was male, 68 years old, the tribe of Bali, a Hindu came on January 7, 2015 with complaints of pain in the gut for a long time which is about 6 months ago and was advancing from + 2 days ago. Pain feels like a tingling blunt and does not spread, the patient felt throughout the day. Pain initially appears suddenly, felt increasingly become heavy to interfere with the patient's daily activities. The pain did not diminish after patients eat and with drugs. Patients also complained of pain he felt increasingly growing, especially at night.